Development and validation of the Social Capital Assessment Tool in pregnancy for Maternal Health in Low and middle income countries (LSCAT-MH) - Nick Glozier; Thilini C Agampodi; Suneth B Agampodi; T A Lelwala; K D P S Sirisena; Sisira Siribaddana (BMJ Open)
Objectives Social capital which implies ‘features of social organisation, such as trust, norms and networks that can improve the efficiency of society by facilitating coordinated actions’ is rarely assessed in relation to maternal health in low/middle-income countries (LMICs). A main reason for this research gap could be the unavailability of a specific tool to measure social capital in pregnancy. The study developed and validated an instrument to measure social capital among pregnant women.Setting We developed the tool based on World Bank Social Capital Assessment Tool and its adaptations identified as applicable to LMIC from an initial systematic review. The study was conducted in Anuradhapura district in the North Central Province of Sri Lanka. Validation process was conducted in urban, rural and resettled communities.Participants Study participants of the cognitive validation included pregnant women from the three communities, and an expert panel including a social scientist, methodological expert, subject expert, public health officers. The psychometric validation was performed on 439 pregnant women permanently residing in the three communities.Results The 24-item Low and middle income countries Social Capital Assessment Tool for Maternal Health (LSCAT-MH) demonstrated high internal consistency (Cronbach’s α=0.94). Factor analytical methods suggested a four-factor model of (1) neighbourhood networks (structural bonding), (2) domestic and neighbourhood cohesion (cognitive bonding), (3) social contribution and (4) social participation (structural bridging). Concurrent validity with antenatal mental ill health was confirmed through a negative correlation with the Edinburgh Postpartum Depression Scale. Test–retest reliability was high with intraclass correlation of 0.71 and a Pearson correlation of 0.83.Conclusion The LSCAT-MH is a psychometrically valid and reliable tool to measure social capital in pregnancy. Predictive validity was not tested as the study was not a longitudinal follow-up.